2018
DOI: 10.1039/c8fo01436a
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of sesamol on systemic oxidative stress-induced cognitive impairments via regulation of Nrf2/Keap1 pathway

Abstract: Sesamol treatment alleviated systemic oxidative stress induced cognitive deficits via improving neuronal impairments, restoring antioxidant activities and up-regulating antioxidative signaling pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 48 publications
4
46
0
Order By: Relevance
“…These findings were consistent with previous studies, which showed that sesamol increased GSH and decreased MDA levels in rat ischemic cortex tissues [24]. Sesamol regulation of GSH and MDA levels also reduced oxidative stress and improved cognitive impairments in mouse brains [54]. Hence, sesamol had a protective effect against oxidative stress, and thus maintained lung function in asthmatic mice.…”
Section: Discussionsupporting
confidence: 92%
“…These findings were consistent with previous studies, which showed that sesamol increased GSH and decreased MDA levels in rat ischemic cortex tissues [24]. Sesamol regulation of GSH and MDA levels also reduced oxidative stress and improved cognitive impairments in mouse brains [54]. Hence, sesamol had a protective effect against oxidative stress, and thus maintained lung function in asthmatic mice.…”
Section: Discussionsupporting
confidence: 92%
“…Reactive oxygen species (ROS), the most important oxygen free radical, is closely related to the pathology and development of various neurodegenerative diseases (Deshmukh, Unni, Krishnappa, & Padmanabhan, 2017). Excessive ROS production disrupts the balance between cellular oxidation and antioxidant defense systems, induces lipid peroxidation, DNA fragmentation, cellular integrity, and functional impairment, and ultimately leads to neuronal function disruption and apoptosis (Finkel & Holbrook, 2000; Ren et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the Keap1-hypo allele (Nrf2 activation) mice were partially protected from obesity, had lower fasting glucose and insulin levels, and developed less liver steatosis [40]. In addition, sesamol has been shown to protect cognitive impairments by activating the Nrf2 transcriptional pathway [41]. Therefore, the identification of a potent Nrf2 activator may provide another tool to prevent obesity and its associated metabolic diseases by enhancing energy expenditure.…”
Section: Discussionmentioning
confidence: 99%